The Skeleton of Lateral Meningocele Syndrome - Canalis, Ernesto (Frontiers in Genetics, 2021)
Notch (Notch1 through 4) are transmembrane receptors that determine cell differentiation and function, and are activated following interactions with ligands of the Jagged and Delta-like families. Notch has been established as a signaling pathway that plays a critical role in the differentiation and function of cells of the osteoblast and osteoclast lineages as well as in skeletal development and bone remodeling. Pathogenic variants of Notch receptors and their ligands are associated with a variety of genetic disorders presenting with significant craniofacial and skeletal manifestations. Lateral Meningocele Syndrome (LMS) is a rare genetic disorder characterized by neurological manifestations, meningoceles, skeletal developmental abnormalities and bone loss. LMS is associated with NOTCH3 gain-of-function pathogenic variants. Experimental mouse models of LMS revealed that the bone loss is secondary to increased osteoclastogenesis due to enhanced expression of receptor activator of nuclear factor kappa B ligand by cells of the osteoblast lineage. There are no effective therapies for LMS. Antisense oligonucleotides targeting Notch3 and antibodies that prevent the activation of NOTCH3 are being tested in preclinical models of the disease. In conclusion, LMS is a serious genetic disorder associated with NOTCH3 pathogenic variants. Novel experimental models have offered insight on mechanisms responsible and ways to correct the disease.